2020
DOI: 10.1139/cjb-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of the heat-stress response in Boechera depauperata and Arabidopsis reveals a distinct and unusual heat-stress response in Boechera

Abstract: Global surface temperatures are expected to rise throughout the 21st century and will negatively impact plant growth and reproduction. Thus, it is imperative that we deepen our understanding of plant thermotolerance. The examination of native plant species that have evolved tolerance to high temperatures can provide crucial information on how plants can adapt to climate change. Boechera (Brassicaceae), a large genus that is native to North America, is highly thermotolerant and can maintain photosynthetic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The study found that Arabidopsis mutants lacking PIFs transcription factors exhibited elongation and rapid growth cessation in simulated shading experiments. More and more scientists were placing greater emphasis on the relationship between plants and the environment, especially in terms of climate ( Méndez-Vigo et al., 2019 ; Pierce et al., 2020 ). Therefore, in the future, Arabidopsis thaliana research at the micro level holds the promise of providing a basis for improving the global environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that Arabidopsis mutants lacking PIFs transcription factors exhibited elongation and rapid growth cessation in simulated shading experiments. More and more scientists were placing greater emphasis on the relationship between plants and the environment, especially in terms of climate ( Méndez-Vigo et al., 2019 ; Pierce et al., 2020 ). Therefore, in the future, Arabidopsis thaliana research at the micro level holds the promise of providing a basis for improving the global environment.…”
Section: Discussionmentioning
confidence: 99%
“…between plants and the environment, especially in terms of climate (Meńdez-Vigo et al, 2019;Pierce et al, 2020). Therefore, in the future, Arabidopsis thaliana research at the micro level holds the promise of providing a basis for improving the global environment.…”
Section: The Prominent Position Of Arabidopsis Thalianamentioning
confidence: 99%